Twenty-five years of legal education at the IIUM - Rashid, Syed Khalid (IIUM Press, 2009)
Introduction : With its 120-strong teaching staff, supported by 26 administrative staff and a total student population of 2,500, the Ahmad Ibrahim Kulliyyah of Laws (AlKOL) is perhaps the biggest law faculty in South-East Asia. From its humble beginnings in 1983, with 3 teaching staff and 59 students, it has indeed made impressive progress. What makes the law programme at the International Islamic University Malaysia (IIUM) unique, is the combining of sharf'ah and common law courses, enabling its graduates to practise law at the civil as well as shartah courts...